Feasibility of salt pads to improve fat suppression in low-field MRI systems - Sakoda, K.; Oura, R.; Baba, S. (Radiography (London, England. 1995), 2022)
Fat-suppressed images are essential in clinical practice but are often affected by magnetic field inhomogeneity, resulting in poor image quality. We hypothesized that salt (99% sodium chloride [NaCl]) could be used as a magnetic field uniformity assist pad and verified whether salt pads improve magnetic field uniformity and the fat suppression effect in low-field magnetic resonance imaging (MRI) systems. We conducted a small clinical study where coronal 2D fast spin-echo T2-weighted MRI with fat suppression was performed. The subjects were 10 healthy volunteers (six men and four women) with no surgical history, with a mean age of 20.5 years (range, 20–30 years). In the clinical study, we performed physical and visual evaluation by imaging a subject's knee with and without salt pads. The results of the clinical study indicated that the use of salt pads improved the magnetic field uniformity, thus increasing the fat suppression effect. Salt pads improved the homogeneity of the magnetic field and the fat suppression effect in low-field MRI systems. The use of salt pads in low-field MRI systems could provide more accurate fat suppression images.